3D focusing acoustic lens optimization method using multi-factor and multi-level orthogonal test designing theory. (15th December 2020) - Sun, Hongyu; Wang, Shen; Huang, Songling; Peng, Lisha; Wang, Qing; Zhao, Wei; Zou, Juna
Abstract: Focusing systems that consist of acoustic lenses exhibit higher controllability and focusing intensity when manipulating sound waves. Different parameters have different effects on the performance of the acoustic lens, so analyzing a variety of parameter combinations for the acoustic lens is difficult because of the complexity of the test. Therefore, we report an analytical method for studying the focusing performance of different factors on acoustic lenses at different levels, and the influence degree of each factor is investigated through range analysis. Results show that the factors that have the most significant influence on the focusing intensity, focal-area dimensions, and focal length are the incident sound field's pressure P 0, cell dimension c, and cell edges k, respectively. Moreover, the effects of other parameters, including the biased incident-wave angles, are obtained and analyzed through finite-element simulations. After analyzing and comprehensively comparing the influences of various parameters, the optimal parameter combination is obtained to achieve the best focusing performance of an acoustic lens. The experimental results show that the focusing intensity of the optimized acoustic lens is nearly 90% higher than the non-optimized one, which proves the effectiveness of the orthogonal test-optimization method in this paper.